Aquasomes: A Novel Drug Carrier - Sanjay S. Jain, Pramod S. Jagtap, Neha M. Dand, Kisan R. Jadhav, Vilasrao J. Kadam (Journal of Applied Pharmaceutical Science)
Aquasomes are one of the most recently developed delivery system for bioactive molecules like peptide, protein, hormones, antigens and genes to specific sites. Aquasomes are spherical in shape with 60–300 nm particles size. These are nanoparticulate carrier systems but instead of being simple nanoparticles these are three layered self assembled structures, comprised of a solid phase nanocrystalline core coated with oligomeric film to which biochemically active molecules are adsorbed with or without modification. These structures are self assembled by non covalent and ionic bonds. The solid core provides the structural stability, while the carbohydrate coating protects against dehydration and stabilizes the biochemically active molecules. The delivery system has been successfully utilized for the delivery of insulin, hemoglobin, and enzymes like serratiopeptidase etc. This reviews the principles of self assembly, the challenges of maintaining the conformational integrity and biochemical activity of immobilized surface pairs, the convergence of these principles into a single functional composition and its application in various fields of pharmacy.
Keywords: Bioactive molecules, Nanoparticulate carrier system, Oligomeric film, Carbohydrate, Self assembly, Conformational integrity